Pengujian Ekstrak Sederhana Bagian Tumbuhan Cassia alata Linnaeus terhadap Colletotrichum Gloeosporioides secara Invitro: Bahasa Inggris - Arneti, Arneti; Sulyanti, Eri (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2017)
Plant extracts have been known to cause inhibit the growth of Colletotrichum gloeosporioides.This study was aimed to determine the most potential part of Cassia alata crude extract to control antrachnose on chili. The study was conducted in Phytopathology Laboratory, Plant Pests and Diseases Department, Agriculture Faculty, Andalas University, from April to June 2015. The research used Completely Randomized Design (CRD) with seven treatments and five replications. The treatments were several extracts from different parts of C. Alata: 1) control 2) flower, 3) old leaf, 4) young leaf, 5) stem, 6) root, and 7) seed with concentration of 5% respectively. Variables observed were colony growth, colony width, conidia number, colony wet and dry weight, and conidia germination. The result showed that all of C. alata extracts could inhibit the growth of C. gloeosporioides in vitro. The best extract was from the old leaf with the percentage of colony width, conidia number, colony wet and dry weight, and conidia germination of 64,30%, 82,41%, 37,77, 29,8%, and 79,96% respectively.